2015
DOI: 10.1088/1757-899x/102/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Conductance Degradation in HTS Coated Conductor Solder Joints

Abstract: Abstract. Solder joints between YBCO coated conductors and normal metal traces have been analysed as part of an effort to develop a robust HTS lead assembly for a spaceflight mission. Measurements included critical current and current transfer profiles. X-ray micrographs were used to verify proper solder flow and to determine the extent of voiding. SEM of crosssections with EDS analysis was crucial in understanding the diffusion of the protective silver layer over the YBCO into the solder for different solder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Much of this improvement comes from manufacturing process changes since SXS. Given the long period of air exposure from the time of manufacture to the time of test, all evidence implies any degradation in the original critical current is most likely due to stresses in handling of these narrow, 1 mm wide tapes and sudden liquid nitrogen cool down, rather than to a slow process (see [6]). Indeed, the only two tape samples that showed Ic below the limit to which all the samples were tested before shipment (20 Amp) were two that were used in the development of the installation process for the test rigs; most samples had Ic well above this limit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this improvement comes from manufacturing process changes since SXS. Given the long period of air exposure from the time of manufacture to the time of test, all evidence implies any degradation in the original critical current is most likely due to stresses in handling of these narrow, 1 mm wide tapes and sudden liquid nitrogen cool down, rather than to a slow process (see [6]). Indeed, the only two tape samples that showed Ic below the limit to which all the samples were tested before shipment (20 Amp) were two that were used in the development of the installation process for the test rigs; most samples had Ic well above this limit.…”
Section: Discussionmentioning
confidence: 99%
“…Early versions of the assemblies showed degradation of solder joint conductance with time. Analysis of solder joint samples showed that diffusion of indium from the indium-silver solder into Ag5%Au layer protecting the REBCO led to direct contact of indium with the REBCO layer, which is known to degrade the Ic [6]. This problem was avoided for RESOLVE by plating the regions of the tape around the solder joint with a heavy (~ 20 µm) layer of copper, which effectively blocked indium diffusion, while maintaining the very low thermal conductance of the unplated tape between the solder joints.…”
mentioning
confidence: 99%
“…Once melted, solders containing Sn and In can rapidly consume the thin silver stabilizer layer and harmfully react with the HTS film. Canavan et al reported on how melted In3%Ag solder rapidly diffuses into the thin silver stabilizer film of standard CCs and can form continuous intermetallic compound (IMC) phases in contact with the REBCO film that causes cracks and considerably increases 𝜌𝜌 𝑐𝑐 [21].…”
Section: Introductionmentioning
confidence: 99%